SOCIAL-PSYCHOLOGICAL FACTORS OF THE INFLUENCE OF TEACHERS' PSYCHOLOGICAL HEALTH ON THE EDUCATIONAL PROCESS - М. Khakimova (Bright Mind Publishing, 2025)
This article discusses the social-psychological factors influencing the impact of teachers' psychological health on the educational process. It presents the idea that a teacher’s professional activity is closely connected to their mental well-being.
Keywords: Teacher, profession, mental health, consciousness, fatigue, education, factors, norms, efficiency, activity.